Pengaruh Kompensasi Gaji dan Tunjangan Terhadap Motivasi Karyawan di PT. Perkebunan Nusantara II (Persero) Tanjung Morawa Kabupaten Deli Serdang - Widya Sari Putri Sitanggang (Mahesa Research Center, 2023)
Salary is a form of appreciation or remuneration from the employer provided periodically to workers for their services or work results. A person receives a salary if their work relationship is strong with an organization. Salary comprises various components, including basic salary, meal allowances, transportation allowances, other benefits, all contingent upon the company's policies. Allowances are an additional type of compensation provided by almost all organizations. These allowances are vast and essential, especially in enhancing the welfare of employees. They are not based on employee performance but on their membership within the organization, recognizing employees as individuals with numerous needs to lead a normal life and perform optimally, ensuring security from potential job termination risks, addressing health issues, allowing breaks from work, and fostering comfortable interactions with others